Shear-induced detachment of polystyrene beads from SAM-Coated Surfaces - Cho, Kwun Lun; Rosenhahn, Axel; Thelen, Richard; Grunze, Michael; Lobban, Matthew; Karahka, Markus Leopold; Kreuzer, H. Jürgen (Langmuir, 2015)
In this work we experimentally and theoretically analyze the detachment of microscopic polystyrene beads from different self-assembled monolayer (SAM) surfaces in a shear flow in order to develop a mechanistic model for the removal of cells from surfaces. The detachment of the beads from the surface is treated as a thermally activated process applying an Arrhenius Ansatz to determine the activation barrier and attempt frequency of the rate determing step in bead removal. The statistical analysis of the experimental shear detachment data obtained in phosphate-buffered saline buffer results in an activation energy around 20 kJ/mol, which is orders of magnitude lower than the adhesion energy measured by atomic force microscopy (AFM). The same order of magnitude for the adhesion energy measured by AFM is derived from ab initio calculations of the van der Waals interaction energy between the polystyrene beads and the SAM-covered gold surface. We conclude that the rate determing step for detachment of the beads is the initiation of rolling on the surface (overcoming static friction) and not physical detachment, i.e., lifting the particle off the surface.
Gesehen am 30.11.2020